2022
DOI: 10.37765/ajmc.2022.89211
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in kidney function testing and associations with health care costs among patients with chronic kidney disease and type 2 diabetes

Abstract: S105VALIDATION OF THE FINE-CKD MODEL placebo. 8 Based on the FIDELITY results, on top of the maximum tolerated renin-angiotensin system inhibitor (RASi) treatment, finerenone showed substantial benefits for a range of CV and renal outcomes. 11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Yet, several studies from primary-care practices showed the underutilization of tests, inadequate recognition, and undercoding of CKD patients, even in those with high-risk conditions (16,(23)(24)(25)(42)(43)(44). In the CURE-CKD registry, nearly one half of patients with persistently low eGFR remained undiagnosed in 2014-2017 (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, several studies from primary-care practices showed the underutilization of tests, inadequate recognition, and undercoding of CKD patients, even in those with high-risk conditions (16,(23)(24)(25)(42)(43)(44). In the CURE-CKD registry, nearly one half of patients with persistently low eGFR remained undiagnosed in 2014-2017 (22).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, considerable efforts have been made to increase the awareness of CKD, to timely detect and deliver proper care to identified CKD patients. CKD is still often under-detected, even amongst patients with high-risk conditions (e.g., DM, hypertension, or CVD) (22)(23)(24)(25), where screening for CKD is recommended by regularly testing eGFR and albuminuria (10,21,26).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of knowledge can hinder the diagnosis of early CKD, as well as an appropriate risk stratification of patients. Other barriers include the limited involvement of primary care in management of CKD, a lack of proper nephrology consults based on target GFR and lack of clinician- or patient-targeted evidence-based interventions to reduce CKD progression or CVD, the existence of few partnerships between a clinician and patient, and insufficient tools for utilizing electronic health records (EHRs) [ 11 , 12 , 67 , 68 , 69 ].…”
Section: Overcoming Barriers To Ckd Care Deliverymentioning
confidence: 99%